2013
DOI: 10.1007/s00248-013-0327-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Grazer Presence on Genetic Structure of a Phenotypically Diverse Diatom Population

Abstract: Studies of predator-prey systems in both aquatic and terrestrial environments have shown that grazers structure the intraspecific diversity of prey species, given that the prey populations are phenotypically variable. Populations of phytoplankton have traditionally considered comprising only low intraspecific variation, hence selective grazing as a potentially structuring factor of both genetic and phenotypic diversity has not been comprehensively studied. In this study, we compared strain specific growth rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Another, more recent study examined the functional diversity of the marine diatom Skeletonema marinoi by observing the potential effects of grazing pressure (reflected by different grazer levels) (Sjöqvist et al, 2013). The study confirmed that genetically distinct individuals of S. marinoi are functionally more diverse.…”
Section: Classical Biodiversity Indicesmentioning
confidence: 76%
“…Another, more recent study examined the functional diversity of the marine diatom Skeletonema marinoi by observing the potential effects of grazing pressure (reflected by different grazer levels) (Sjöqvist et al, 2013). The study confirmed that genetically distinct individuals of S. marinoi are functionally more diverse.…”
Section: Classical Biodiversity Indicesmentioning
confidence: 76%
“…Baltic low-salinity-adapted populations of the species are genotypically diverse and display considerable phenotypic diversity (Sjöqvist et al, 2014(Sjöqvist et al, , 2015. Using microsatellite-based genotyping methods we were able to monitor and confirm true clonal diversity in experimental mixtures.…”
Section: Introductionmentioning
confidence: 89%
“…For example, blooms of S. marinoi consist of genetically distinct clones that differ largely in growth characteristics and cell chain morphology (Sjöqvist et al, 2014). Other phytoplankton species vary intraspecifically in environmental tolerances (Gsell et al, 2012;Ribeiro et al, 2013;Skjelbred et al, 2013) and cellular toxicity (Suikkanen et al, 2013).…”
Section: Phenotypic Differences Among Strainsmentioning
confidence: 99%
“…Copepods of the genus Acartia , instead, have been reported to be able to discern their prey by detecting cell composition (e.g., Poulet and Marsot , Sjöqvist et al. ); the experimental evidences in support of this, however, are quite indirect (as argued in the introduction of this paper) and less ambiguous results would be required to demonstrate the ability of copepods to select algae based on their cell content.…”
Section: Discussionmentioning
confidence: 89%